Structural and functional analyses of antibodies specific for modified core N‐glycans suggest a role in TH2 responses. Issue 1 (1st July 2022) - Plum, Melanie; Tjerrild, Luna; Raiber, Tim; Bantleon, Frank; Bantleon, Sara; Miehe, Michaela; Jabs, Frederic; Seismann, Henning; Möbs, Christian; Pfützner, Wolfgang; Jakob, Thilo; Andersen, Gregers R.; et al.
Abstract: Background: Immune responses to N‐glycan structures from allergens and parasites are often associated with pronounced, high affinity IgE reactivities. Cross‐reactive carbohydrate determinants (CCDs) are constituted by modified N‐glycan core structures and represent the most frequently recognized epitopes in allergic immune responses. Although recently accepted as potentially allergenic epitopes, the biological and clinical relevance as well as structural and functional characteristics of CCD‐specific antibodies remain elusive. Methods: In order to gain structural insights into the recognition of CCDs, two specific antibody fragments were isolated from a leporid immune repertoire library and converted into human/leporid IgE and IgG formats. The antibody formats were assessed by ELISA and surface plasmon resonance, structural and functional analyses were performed by X‐ray crystallography, mediator release, and ELIFAB assays. Results: The recombinant IgE exhibited highly specific interactions with different types of CCDs on numerous CCD‐carrying glycoproteins. Crystal structures of two CCD‐specific antibodies, one of which in complex with a CCD‐derived disaccharide emphasize that mechanisms of core glycan epitope recognition are as specific as those governing protein epitope recognition. The rIgE triggered immediate cellular responses via FcεRI cross‐linking and mediated facilitated antigen presentation by binding of IgE/antigen complexes to CD23, a process that also could be blocked by IgG of allergic patients. Conclusions: Our study provides evidence for the relevance of N‐glycan recognition in TH 2 responses and corroborates that IgE and IgG antibodies to ubiquitous carbohydrate epitopes can be equivalent to those directed against proteinaceous epitopes with implications for diagnostic and immunotherapeutic concepts. Abstract : Monoclonal antibody fragments with specificity for CCD structure were generated. Derived CCD‐specific IgE detect CCD‐carrying allergens and are capable for mediating effector cell activation and facilitated allergen binding. A Fab in complex with an epitope surrogate provides direct insights into the binding mode of CCDs.Abbreviations: CCD, cross‐reactive carbohydrate determinant; Fab, fragment antigen binding; HRP, horseradish peroxidase; MUXF, the N‐glycan from bromelain